O014 Heart rate response to obstructive respiratory events in children born preterm with OSA. (7th October 2021) - Walter, L; Bassam, A; Davey, M; Gillian, N; Horne, R
Abstract: Background: Preterm-born (PT) children have an increased risk for obstructive sleep apnoea (OSA) and adverse cardiovascular outcomes. Respiratory events elicit acute changes in heart rate (HR) in term-born (T) children. Whether this response is augmented in PT children with OSA remains unclear. We aimed to analyse the HR response during obstructive respiratory events in PT children with OSA. Methods: Nine PT children (3–12 y), were matched for obstructive apnoea hypopnoea index (OAHI), age and gender with T children. Beat-to-beat HR was averaged 10s before, during and the peak after (post) each obstructive event, and peak HR was expressed as percentage change. Results: 323 obstructive events in PT and 376 in T children were identified, consisting of 681 hypopnoeas (PT 320; T 361) and 18 apnoeas (PT 3; T 15). There were insufficient apnoeas in the PT group for analysis. For hypopnoeas during total sleep, the PT group had significantly lower HR compared to the T group before median 81bpm (IQR 74–87) vs 88 bpm (79–99); p<0.001), during (76 bpm (69–83) vs 82 bpm (74–92; p<0.001) and post (97 bpm (89–103) vs 105 bpm (95–115; p<0.001) events. The post event increase in HR was significantly higher in the PT (26%, (16–39)) compared with the T (23%, (14–36)) group, p=0.008. Conclusion: Although HR was lower during obstructive hypopnoeas in preterm compared with term-born children, the post event surge was significantly higher. This heightened HR response to respiratory events in children born preterm may underlie the worse cardiovascular outcomes in these children.